Perspectives on the Origin and Essence of the Modern State - Vande, Philip T. (Kashere Journal of Politics and International Relations, 2025)
The State is the dominant form of political organisation and rules the world today. It has become a consistent presence that affects daily lives almost constantly. The modern State has become a complex outfit for meeting all sorts of needs of the citizens. Over the years, fundamental and critical questions were raised on the origin and essence of the State. These have produced generations of remarkable scholarship in the discipline of social sciences. This study, relying on extant literature, crystallises the various perspectives of the modern State, explaining the liberal and radical ideas of the State. The Social Contract Theory and the Marxist Theory were examined. More so, the essence of the State, a subject of endless debate among political theorists was presented. The study also related the essence of the State to citizens’ obligations. It concluded that the essence of the State is a complex and multifaceted theme, yet, one way to understand the essence of the State is to examine its functions concerning the citizens. The study recommends that for the State to be worth its salt, it must demonstrate its capacity, maintain law and order, protect citizens from external threats, provide public goods and services, and promote the general welfare of its citizens. The State should also regulate the economy, redistribute wealth, and enforce social norms.